Legal Consequences of the Responsibility of Land Deed Officials (PPAT) in Verifying Seller and Buyer Taxes for Transfer of Land Rights in Semarang Regency - Alifati, Izta Aulia; Purnawan, Amin (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to reveal the extent of the responsibility of the Land Deed Official (PPAT) in the context of the PPAT's accountability in verifying the seller's and buyer's taxes on the transfer of land rights, as well as the legal consequences of the PPAT's accountability in verifying the seller's and buyer's taxes on the transfer of land rights if the tax payment value differs from the selling price. This type of research is a sociological juridical legal research. The results show that the PPAT has a legal obligation to verify the accuracy of the Income Tax (PPh) and Land and Building Acquisition Fee (BPHTB) payment data before signing the deed of transfer of rights. If there is a difference in the value between the tax payment and the selling price, the PPAT remains administratively and morally responsible to ensure that the data is in accordance with the actual transaction. The legal consequences that arise can be the cancellation of the deed, administrative sanctions against the PPAT, or losses to the state due to potential reductions in tax revenue. Keywords: Land Deed Official; Legal Responsibility; Tax Verification; Transfer of Land Rights.